French adaptation of the Short Dark Triad: Psychometric properties and a head-to-head comparison with the Dirty Dozen. (1st February 2018) - Gamache, Dominick; Savard, Claudia; Maheux-Caron, Véronique
Abstract: Research on the Dark Triad (DT), a term coined to describe three socially aversive personality traits (Machiavellianism, narcissism, and psychopathy), has grown exponentially over the past years, in part due to the dissemination of two short, valid measures of the construct: the Short Dark Triad (SD3), and the Dirty Dozen (DD). The goal of this study is to report on the psychometric properties of a French adaptation of the SD3 (N = 405). Analyses include classical psychometric properties assessment, with a head-to-head comparison with the competing DD. The French SD3 showed good basic psychometric qualities. Factor structure was optimally represented by a bifactor model, as most items load both on their respective trait factor and on an overarching DT factor. There were significant, conceptually meaningful associations with measures of psychopathic traits, pathological narcissism, empathy, impulsivity, and social desirability. The SD3 showed incremental convergent validity over the DD for most variables, notably antisociality and impulsivity; however, the DD showed stronger positive association with pathological narcissism and stronger negative association with empathic concern. Overall, the French SD3 possesses sound psychometric properties, comparable with the original version. The relative merits of the SD3 and the DD for research and screening purposes are discussed. Highlights: The study reports on the psychometric properties of the French Short Dark Triad (SD3). Overall, the translation showed sound psychometric properties. Factor structure was optimally represented by an ESEM bifactor model. It had incremental validity over the French Dirty Dozen (DD) for most external criteria. However, both the SD3 and the DD appear to have their strengths and merits.